(untitled) (Research, Society and Development, 2021)
Objective: To describe the impact of leprosy on the quality of life of patients. Methods: This is an integrative literature review carried out in the Scientific Electronic Library Online (SciELO) and Nursing Database (BDENF) databases. As inclusion criteria: articles that address the theme, in the last ten years. As exclusion criteria: articles that did not cover the topic. Eighty-five studies were found in the selected databases and after applying the inclusion and exclusion criteria, 11 studies were selected to compose the review. Results: Leprosy is a transmissible disease that affects the peripheral nerves and the skin, and can cause serious sensory, motor and autonomic damage. It results from the individuals’ susceptibility, genetic predisposition or prolonged contact with untreated leprosy patients. It is known that leprosy is currently curable and its treatment is offered through the Unified Health System (SUS), however factors such as stigma, prejudice and lack of information delay the process of curing the disease and bring challenging consequences in the context of public health. Final Considerations: Therefore, it is pertinent to discuss the problem, in order to identify strategies that better minimize the impact of leprosy on the lives of patients and the side effects for the community.